The Stories that Make Us: European Holocaust Narratives and the Promise of Albanian Cosmopolitan Memory Practices - Kailey rocker (Kosova Anthropologica)
In this paper, I explore how Holocaust memorial narratives are utilized in the contemporary Albanian context – to engage the country’s direct relationship with that history as well as debates over how to count, mourn, and represent those lost during the country’s socialist regime, from 1944 to 1991. In particular, I focus on post-1991 efforts by local historians and politicians as well as foreign amateur and expert historiographers to exemplify Albania as a safe haven for the Jewish community during the Second World War and more recent efforts to commemorate the socialist era Tepelena Internment Camp, which took on the unofficial name of Albania’s Auschwitz during my fieldwork. I approach these narratives through the lens of memory appropriation (Subotić 2019) to understand how Albanian narratives contribute to the de-territorialization and de-contextualization of what Levy and Sznaider (2002) call a cosmopolitan memory culture. I argue that both appropriations, while different, ultimately speak to the intersection of the following tracks: Albanian efforts to participate in broader European memoryscapes through the reproduction of their own nationally specific narratives and broader European efforts to secure memory narratives through the inclusion of southeastern European ones.